Canadian International Petroleum Conference 2003
DOI: 10.2118/2003-199
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Mechanistic Simulations to Design an ASP Field Pilot in La Salina, Venezuela

Abstract: In La Salina field, located in the Maracaibo Lake, Venezuela, which produces a medium gravity crude oil (25 ° API) from a Miocene reservoir at 3,000 feet, a series of EOR processes were proposed to be evaluated under field conditions. Results from laboratory tests indicated that Alkali-Surfactant-Polymer technology (ASP) might be a potential EOR process to improve the oil recovery factor. However, ASP processes involve the injection of a significant volume of chemicals, therefore, costs associated with this te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The EOR studies on the Caracara Sur field in Llanos Basin, Columbia were conducted, but a field pilot or an application has not been seen reported. Several papers have been presented about the design and preparation of the offshore ASP pilots in two fields, St. Joseph in Malaysia and La Salina in Venezuela . The field application results have not been seen reported in the literature.…”
Section: Summary Of Pilots and Large‐scale Applicationsmentioning
confidence: 99%
“…The EOR studies on the Caracara Sur field in Llanos Basin, Columbia were conducted, but a field pilot or an application has not been seen reported. Several papers have been presented about the design and preparation of the offshore ASP pilots in two fields, St. Joseph in Malaysia and La Salina in Venezuela . The field application results have not been seen reported in the literature.…”
Section: Summary Of Pilots and Large‐scale Applicationsmentioning
confidence: 99%
“… 21 Using commercial simulation software CMG to design and simulate field pilot, Moreno et al and Van et al indicated that it is possible to increase oil recovery dramatically by ASP flooding. 22,23 Farajzadeh et al coupled a multi-purpose dynamic reservoir simulator (MoReS) and geochemistry software program (PHREEQC) to provide a versatile tool for ASP flooding numerical simulation. 24 …”
Section: Introductionmentioning
confidence: 99%